Innovation capabilities for sustainable development in Africa - Keun Lee; Calestous Juma; John Mathews (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
A sustainable pathway for Africa in the twenty-first century is laid out in the setting of the development of innovation capabilities and the capture of latecomer advantages. Africa has missed out on these possibilities in the twentieth century while seeing the East Asian countries advance. There are now abundant examples and cases to draw on, in the new setting where industrial development has to have green tinges to be effective.
Keywords: O14; O25; O33; O55; 330; Africa; sustainable development; innovation capabilities; green growth strategy; latecomer advantages